2013
DOI: 10.5713/ajas.2012.12561
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Plasma Fatty Acids, Villous Height and Crypt Depth of Preweaning Piglets Fed with Medium Chain Triacylglycerol

Abstract: A study was conducted to investigate the effects of feeding medium chain triacylglycerol (MCT) on growth performance, plasma fatty acids, villus height and crypt depth in preweaning piglets. A total of 150 new born piglets were randomly assigned into one of three treatments: i) Control (no MCT); ii) MCT with milk (MCT+milk); iii) MCT without milk (MCT+fasting). Body weight, plasma fatty acid profiles, villus height and crypt depth were measured. Final BW for the Control and MCT+fasting was lower (p<0.05) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 14 publications
3
50
0
4
Order By: Relevance
“…Therefore, both additives (RPEO and chlorohydroxyquinoline) improved villi health, compensating for the lowered VD, providing similar growth performance to the negative control. Previous studies have shown that higher VD does not always result in higher nutrient absorption rates, once enterocyte maturity also plays a key role in the absorption rate.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, both additives (RPEO and chlorohydroxyquinoline) improved villi health, compensating for the lowered VD, providing similar growth performance to the negative control. Previous studies have shown that higher VD does not always result in higher nutrient absorption rates, once enterocyte maturity also plays a key role in the absorption rate.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, oil improves the absorption of oilsoluble vitamins, increases the palatability of rations, reduces pulverulence, increases the efficiency of the consumed energy (Baiao & Lara 2005;Chwen et al 2013) and also reduces the rate of passage of digesta in the gastrointestinal tract, which gives room for adequate and efficient absorption of the nutrients present in such diet (Baiao & Lara 2005). Furthermore, the fatty acid profile of muscle tissue reflects the dietary fatty acid profile (Abdulla et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence fat is widely used in broiler diets to meet the energy requirements of fast growing modern strains (Baião & Lara, 2005). In addition, dietary fats enhance the absorption and utilization of fat-soluble vitamins, increase the palatability of rations, reduce pulverulence, improve the efficiency of the energy consumed (Baião & Lara, 2005;Zulkifli et al, 2007;Chwen et al, 2013) and reduce the rate of passage of digesta in the gastrointestinal tract, which gives room for adequate and efficient absorption of the nutrients present in such diets (Baião & Lara, 2005). Moreover, the fatty acid profile of muscle tissue reflected the dietary fatty acid profile (Maroufyan et al, 2013;Abdulla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%